Botulinum toxin type A as an adjunct to the surgical treatment of the medial rotation deformity of the shoulder in birth injuries of the brachial plexus - Price, A E; Ditaranto, P; Yaylali, I; Tidwell, M A; Grossman, J A I (Journal of bone and joint surgery. British volume, 2007)
We retrospectively reviewed 26 patients who underwent reconstruction of the shoulder for a medial rotation contracture after birth injury of the brachial plexus. Of these, 13 patients with a mean age of 5.8 years (2.8 to 12.9) received an injection of botulinum toxin type A into the pectoralis major as a surgical adjunct. They were matched with 13 patients with a mean age of 4.0 years (1.9 to 7.2) who underwent an identical operation before the introduction of botulinum toxin therapy to our unit. Pre-operatively, there was no significant difference (p = 0.093) in the modified Gilbert shoulder scores for the two groups. Post-operatively, the patients who received the botulinum toxin had significantly better Gilbert shoulder scores (p = 0.012) at a mean follow-up of three years (1.5 to 9.8). It appears that botulinum toxin type A produces benefits which are sustained beyond the period for which the toxin is recognised to be active. We suggest that by temporarily weakening some of the power of medial rotation, afferent signals to the brain are reduced and cortical recruitment for the injured nerves is improved.